Chromogranin A and neuron-specific enolase in neuroblastoma: Correlation to stage and prognostic factors. (17th February 2018) - Georgantzi, Kleopatra; Sköldenberg, Erik G.; Stridsberg, Mats; Kogner, Per; Jakobson, Åke; Janson, Eva Tiensuu; Christofferson, Rolf H. B.
ABSTRACT: Chromogranin A (CgA) and neuron specific enolase (NSE) are important markers in adult neuroendocrine tumors (NET). Neuroblastoma (NB) has certain neuroendocrine properties. The aim of this study was to correlate blood concentrations of CgA, chromogranin B (CgB), and NSE to prognostic factors and outcome in children with NB. Blood samples from 92 patients with NB, 12 patients with benign ganglioneuroma (GN), 21 patients with non-NB solid tumors, 10 patients with acute leukemias, and 69 healthy children, were analyzed. CgA concentrations were higher in neonates vs. children older than one month in the control group ( p < 0.0001), and in neonates with NB vs. the control group ( p < 0.01). CgA and NSE concentrations were higher in patients with stages 3 and 4 disease ( p < 0.05 and p < 0.05), in patients having tumors with amplification of MYCN ( p < 0.05 and p < 0.001), or chromosome 1 p deletion ( p < 0.05 and p < 0.05). NSE correlated to the tumor size at diagnosis ( p < 0.001) and to tumor related death ( p < 0.01) in NB. CgA and NSE concentrations were elevated in patients with NB and especially in those with advanced disease. Both CgA and NSE correlated to genetic markers, while only NSE correlated to primary tumor size and outcome in NB. We found that CgA and NSE are clinically valuable tumor markers in NB and they merit prospective clinical evaluations as such.